Chapter 4 Ethics and access when consent must come first - Busher, Hugh; Fox, Alison (Taylor & Francis, 2019)
Formalised procedures to obtain and document informed consent from research participants are at the heart of the shift from informal to formalised research ethics. Critiques claim that the requirements to obtain consent from all potential participants before the onset of a study will make it impossible to do ethnographic research and participant observation in institutional settings such as schools. Drawing on experiences from an ethnographic research project in secondary schools in Norway, the aim of this chapter is to discuss the ethical considerations and, embedded in these, the methodological and analytical challenges involved in doing participant observation in schools where not all pupils and parents have consented to participation in the research. The chapter suggests possible ways forward for tackling these challenges for ethnographic researchers working in schools.